Possibilidades e limites do controle social no Conselho Distrital de Saúde Indígena – CONDISI Cuiabá - Florentino, Silmara Andrade (2016)
This paper presents an analysis of the possibilities and limits of social control in the Indigenous Health District Council in Cuiabá (CONDISI), having as parameter the social control notions and the coloniality of power, being and knowledge. Health councils have become strategic mechanisms to guarantee the democratization of the decision-making power in the Subsystem of Indigenous Healthcare. These health councils should play an important role to guarantee the effective participation of the indigenous people in the decision-making process. A deep reflection on the nuances of this proposal is essential. The challenges faced and the possibilities of active presence of the actors in the construction of the democratic process must be evaluated, highlighting the discussion on the need of empowerment and autonomy of indigenous people that use the Subsystem. In this conjuncture, the Special Indigenous Sanitary District of Cuiabá can be seen as an unique strategy for the encouragement, empowerment and autonomy, since it provides a more active participation in decision-making. Given this assumption, the study aims to analyze the manifestation of the coloniality in the experience of social control via Indigenous Health District Council and to understand the social representation of users of the Special Health District in the city of Cuiabá. To develop this study the minutes of regular and special meetings of the CONDISI, the analysis of laws, ordinances and resolutions related to social control, and bibliographic sources and academic papers related to Social Control and coloniality were used. The study points out that the way colonialism is currently expressed in the effectiveness of social control makes this exercise difficult, since laws, resolutions and norms are not enough, it is necessary to enable the objective conditions to exercise the representation. Among the forms of colonial control, the coloniality of knowledge that characterizes the modernity imposes the eurocentric thinking and disregards the indigenous cultural knowledge. It denies the equal dialogue and makes the forms of indigenous people participation more difficult through the adoption of an operating model less accessible to indigenous representatives. Despite the difficulties experienced in the daily life of the councils, indigenous societies support them and consider them an important space for social control.